Root form as an aid in the diagnosis and prediction of early-onset periodontitis - Childs, Robert John (My University, 2014)
This study was undertaken to investigate the observation that in some subjects w ith early-onset periodontitis there is a peculiar tapering slenderness of root form. This study compares the degree of taper of the roots of maxillary second premolars, and of the distal roots of mandibular first molars of patients with early-onset periodontitis {experimental subjects), with that of the corresponding roots of control subjects. It seeks to determine whether the degree of taper is ascribable to a particular part of the root; whether differences if any are related to gender or to race; and whether the molars or the premolars would be better diagnostic aids to, and predictors of disease. Periapical radiographs of tw enty teeth of each type were selected for the experimental am control groups. Accurate large scale tracings of the root outlines were made from radiographs. Using the mesiodistal widths of the roots at the cemento-enamel junction in the case of the premolars, and at the root bifurcation in the case of the distal roots of the molars as baseline measurements, the degrees of taper of the roots were determined. Statistical comparison of the degrees of taper of roots from experimental subjects with those of the roots of control subjects iv showed strong evidence of a sharper degree of taper in the former; this was more pronounced for the premolars than for the molars. The degree of taper was more marked in the apical half of the roots of experimental molars; but in experimental premolars the increased taper was evident throughout the entire length of the root. In the case of the experimental molar roots, there is a relationship between race and the degree of taper: this highlights the desirability of future studies examining the root forms of racially segregated groups. There is no relationship between gender and the tapering of the experimental molar roots. For premolars the increased taper of experimental teeth is related neither to race nor to gender. Prediction and diagnosis of disease is more reliable with premolars than with molars, because the latter taper more sharply only along a portion of their roots. In an affected individual, the maxillary second premolar appears to be a reliable predictor and an indicator of early-onset periodontitis. The distal root of the mandibular first molar likewise is a predictor and an indicator of early-onset periodontitis; but as its degree of taper is less pronounced and occurs only in the apical half of the root, its reliability in these roles may be diminished.
Thesis (M.Dent)--University of the Witwatersrand, Faculty of Health Sciences, 1998.